Design Applications in a Sederhana Restaurant sales - Perdana, Sandy; Eko Wulandari, Sri Hariani; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Sederhana Restaurant, established in 1994, located on Jl. Kemiri Sentani, Jayapura. Currently Eating Simple has two restaurants with 20 employees and has an average turnover of 15 million rupiah per day for each diner. Eating Simple serve consumer demand for food products typical Padang consumer has the upper, middle or bottom. Purchases can be made by phone or come directly consumers.Eating Simple yet have many obstacles in the sales process, among other things:1. The first obstacle, the recording process inventory. So owners often problems during procurement. This is because the Eating Simple does not have accurate data and facts about some amount of supply of any goods and the goods sold.2. The second constraint, the process of calculating the sale is made every day on the eve of the restaurant closed. Calculation recap the entire results of the transaction manually using a calculator. The cause of the constraint length of the counting process transactions each day. If it still done this way it often happens that the counting error calculation does not deal effectively and efficiently.3. There is no recording of incoming goods procurement. So it is still difficult for the owner to know the procurement of goods daily report.Based on the problems mentioned above, the need for sales application that can reduce errors in data entry, and accelerate the reporting process. The report includes, sales reports, procurement reports and inventory reports. The sales application was made based desktop that does not rely on the Internet network connection